1957
DOI: 10.1177/004051755702700406
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Tearing Failure

Abstract: The tearing failure of materials depends very strongly on the conditions of use or testing which produce the non-uniform tensile stress which causes such failure. In the trapezoid tear test. the stress pattern is determined largely by variables at the disposition of the operator. The effect of these variables on the tearing strength and the relationship of the latter to the shape of the force-elongation curve have been determined. The tear load is given by an equation of the form where g is the modulus. h is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Indeed it has been shown that that the tear strength of fabrics in the trapezoid configuration can be related to the breaking characteristics of the material 21. The discrepancy between tearing and tensile strength loss level due to aging may be attributed in part to the fact that the model of21 assumes a linear force elongation shape and thus neglects the initial crimp removal 22…”
Section: Resultsmentioning
confidence: 99%
“…Indeed it has been shown that that the tear strength of fabrics in the trapezoid configuration can be related to the breaking characteristics of the material 21. The discrepancy between tearing and tensile strength loss level due to aging may be attributed in part to the fact that the model of21 assumes a linear force elongation shape and thus neglects the initial crimp removal 22…”
Section: Resultsmentioning
confidence: 99%
“…They described in detail the problem of tear strength, appropriate measurement methods, and the correlation relationships between the results obtained by different tear methods. Steele and Gruntfest [12] deduced general formulas to predict trapezoid tear strength of woven fabric and designed relevant experiments to confirm the effectiveness of the equations. The relationship among tear strength, dimension of the specimen, and fabric structural parameters were built up by the formulas.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison results showed that tearing strengths obtained from two testing methods differed dramatically and single tongue tearing is much more satisfactory compared with trapezoid method. Steele and Gruntfest (1957) proposed a general equation to relate trapezoid tearing strength to mechanical properties of constituent yarns and geometrical size of tested sample. This formula is particularly suitable to predict the tearing strength for dense texture woven fabrics.…”
Section: Introductionmentioning
confidence: 99%